2016
DOI: 10.1371/journal.pone.0161797
|View full text |Cite
|
Sign up to set email alerts
|

Influences of High-Level Features, Gaze, and Scene Transitions on the Reliability of BOLD Responses to Natural Movie Stimuli

Abstract: Complex, sustained, dynamic, and naturalistic visual stimulation can evoke distributed brain activities that are highly reproducible within and across individuals. However, the precise origins of such reproducible responses remain incompletely understood. Here, we employed concurrent functional magnetic resonance imaging (fMRI) and eye tracking to investigate the experimental and behavioral factors that influence fMRI activity and its intra- and inter-subject reproducibility during repeated movie stimuli. We f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
38
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 38 publications
3
38
0
Order By: Relevance
“…Intersubject correlation was calculated using the ISCtoolbox (Kauppi et al, ). We controlled the possible effect of silent pauses (see the effect of stimulus structure on ISC, Lu, Hung, Wen, Marussich, & Liu ) by modelling the stimulus structure based on the presence of speech as in Lahnakoski et al (). First, ISC matrices were obtained for each brain voxel by calculating all pairwise Pearson's correlation coefficients (r) of the voxel time courses across the subjects, resulting in 120 unique pairwise r‐values.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Intersubject correlation was calculated using the ISCtoolbox (Kauppi et al, ). We controlled the possible effect of silent pauses (see the effect of stimulus structure on ISC, Lu, Hung, Wen, Marussich, & Liu ) by modelling the stimulus structure based on the presence of speech as in Lahnakoski et al (). First, ISC matrices were obtained for each brain voxel by calculating all pairwise Pearson's correlation coefficients (r) of the voxel time courses across the subjects, resulting in 120 unique pairwise r‐values.…”
Section: Methodsmentioning
confidence: 99%
“…Intersubject correlation was calculated using the ISCtoolbox (Kauppi et al, 2010). We controlled the possible effect of silent pauses (see the effect of stimulus structure on ISC, Lu, Hung, Wen, Marussich, & Liu 2016) To reveal the brain areas related to semantic similarity, we predicted the ISC during listening against the semantic similarity (LSA combined with Wordnet). The significance was tested by conducting a representational similarity analysis using the Mantel test (Mantel, 1967;Nummenmaa et al, 2012).…”
Section: Preprocessingmentioning
confidence: 99%
“…Two sessions were obtained in the eyes-closed resting 75 state, and the other two sessions occurred during free-viewing of an identical movie clip (The 76 Good, the Bad, and the Ugly, 1966, from 162:54 to 168:33 min. in the film), as used in prior studies 77 (Hasson, et al, 2004;Lu, et al, 2016). The visual stimulus was presented using the MATLAB 78 Psychophysics Toolbox (Brainard, 1997;Pelli, 1997); it was delivered to the subjects through a 79 binocular goggle system (NordicNeuroLab, Norway) mounted on the head coil.…”
mentioning
confidence: 99%
“…It has 437 experimentally been proven that neural responses to naturalistic stimuli are reliable and 438 widespread (Hasson, et al, 2010; Jääskeläinen, et al, 2008; McMahon, et al, 2015; Mukamel, et 439 al., 2005), and the connectivity patterns that appear during naturalistic activations better reflect 440 spontaneously emerging patterns in the resting-state as compared to controlled, artificially 441 designed stimuli (Wilf, et al, 2017). Our group has shown that by spatiotemporally scrambling 442 the natural stimulus, widely distributed and highly reproducible fMRI responses could not be 443 reproduced without the high-level natural content of the movie; low-level visual features alone 444 significantly reduced the degree and extent of reproducible responses(Lu, et al, 2016).445 Therefore, naturalistic visual stimuli provide rich task-evoked information about neural dynamics446 as compared to more traditional psychophysical stimuli (e.g. Gabor filters).447 Optimally isolating the task-evoked activity is important for studies of rest-task 448 interaction.…”
mentioning
confidence: 99%
See 1 more Smart Citation